2018
DOI: 10.17116/neiro201882113-21
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative and postoperative endocrine disorders associated with pituitary stalk injuries caused by suprasellar growing tumors

Abstract: Given the difference in symptoms associated with compression and surgical transection of the PS, we believe that these two concepts should be clearly distinguished. The PS compression syndrome includes primarily hyperprolactinemia (37% of cases); elimination of PS compression leads to normalization of the PRL level in most patients and is not accompanied by aggravation of hypopituitarism symptoms. The PS transection syndrome in patients with CP and HIA led to the development of panhypopituitarism in all patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Albeit not statistically significant, the analysis of the absolute PRL levels in those with hyperprolactinemia showed the group that developed DI had an average PRL of 52.55 ng/mL compared with 43.72 ng/mL in those that did not develop DI ( P > 0.05). Pathophysiologically, an elevated PRL indicates stalk effect with tumor involvement of the pituitary stalk [ 13 ]. Similar to variability seen with TSH levels [ 14–16 ], two studies have revealed the presence of both interindividual and intrainidividual PRL variation, with the former having a larger variation [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Albeit not statistically significant, the analysis of the absolute PRL levels in those with hyperprolactinemia showed the group that developed DI had an average PRL of 52.55 ng/mL compared with 43.72 ng/mL in those that did not develop DI ( P > 0.05). Pathophysiologically, an elevated PRL indicates stalk effect with tumor involvement of the pituitary stalk [ 13 ]. Similar to variability seen with TSH levels [ 14–16 ], two studies have revealed the presence of both interindividual and intrainidividual PRL variation, with the former having a larger variation [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of anesthesia to patients suffering sellar/suprasellar lesions is a challenge to every anesthesiologist, due to these lesions frequently accompanying with various neurologic and endocrine dysfunction, depending on properties of lesion, and mass effect on adjacent structures [4]. For instance, space-occupying mass may squeeze pituitary stalk, such compression is able to lead to development of endocrine disorders [5]. Meanwhile, sellar/suprasellar tumor might lead to obesity by different pathophysiologic mechanisms and produce various clinical symptoms [6].…”
Section: Introductionmentioning
confidence: 99%